Collaborative Efforts in Recent Performances and Participatory Artworks - Braddock, C; Shingade, B (Informa UK Limited, 2025)
This essay considers collaborative methods from the perspective of an artist and a curator. Our reflections stem from within creative practice processes as a way of exploring modes of knowledge interactions, learning, and collaboration. We reflect on performances and participatory artworks that involve complex social interactions across their planning, making and realisation, and draw on conversations to reveal the volatility and changeability of artworks and curatorial strategies. We emphasise that collaborative, cooperative and participatory methods in visual arts projects are inextricably social and political. We discuss two visual arts performance and participatory projects–Invitation to Dialogue (2019) and Conversation Mat (2022) undertaken at AUT ST Paul St Gallery (renamed Te Wai Ngutu Kākā Gallery) in Tāmaki Makaurau Auckland, aimed at transforming the artistic, curatorial and participatory ego through an exploration of voice. In so doing, we question artistic, curatorial, and participatory ownership and/or dominance. We explore distinctions between project-time and use-time as a way of contrasting designed aspects of collaboration with those that go beyond the control of makers in risky ways. We draw attention to art/life orientations which generate many modes of collaboration. We discuss an attentiveness necessary for attending to the differing speeds of participants.
Keywords: 3601 Art History, Theory and Criticism; 3604 Performing Arts; 36 Creative Arts and Writing; 1905 Visual Arts and Crafts; 3606 Visual arts